2020
DOI: 10.1016/j.bpj.2020.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Stiffness Regulates Multivalent Binding and Liquid-Liquid Phase Separation

Abstract: Multivalent binding is essential to many biological processes because it builds high affinity bonds by using several weak binding interactions simultaneously. Multivalent polymers have shown promise as inhibitors of toxins and other pathogens, and they are important components in the formation of biocondensates. Explaining how structural features of these polymers change their binding and subsequent control of phase separation is critical to designing better pathogen inhibitors and also to understanding diseas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Phase separation occurs at lower protein target concentrations and lower T T as valency and binding affinity are increased. nucleated a stable condensed phase, used a combination of visual inspection, the Binder cumulant, and a collapse in the R g as described in previous work [16]. We used visual inspection to look for the proportion of 10 runs in which a condensed droplet of targets and polymers persisted for the last quarter of the simulation time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phase separation occurs at lower protein target concentrations and lower T T as valency and binding affinity are increased. nucleated a stable condensed phase, used a combination of visual inspection, the Binder cumulant, and a collapse in the R g as described in previous work [16]. We used visual inspection to look for the proportion of 10 runs in which a condensed droplet of targets and polymers persisted for the last quarter of the simulation time.…”
Section: Resultsmentioning
confidence: 99%
“…Polymers longer than the critical loop length see limited increases in avidity with longer degrees of polymerization. In these phase separation simulations, this results in a relatively small increase in binding avidity when N p is increased from 16 to 64 (and a correspondingly smaller change in the phase boundary) than when N p is increased from 4 to 16.…”
Section: Valency and Affinity Of Specific Lock And Key Bondingmentioning
confidence: 90%
See 2 more Smart Citations
“…Another theoretical study found that the solvation of polymeric linkers between binding sites controls whether polymers form a cross-linked gel with or without phase separation [ 6 ]. In previous work, we showed that polymer flexibility or persistence length can change the effective valency and consequently, the phase boundary of multivalent polymers [ 18 ]. In this paper, we further build on the understanding that multivalent polymer characteristics can control the thermodynamics of biocondensates by exploring the effect of non-specific versus specific polymer binding interactions, condensed phase nucleation in smaller systems, and the dynamics of the resulting condensed polymer droplets.…”
Section: Introductionmentioning
confidence: 99%